(untitled) (GEON Journal (Management, Organizations and Business), 2015)
This paper presents and approach to the reality of marketing focusing on the market orientation, relational marketing and the dominant logic of service in Latin-American companies. Through the reading of several documents resulting from research works related to the topics that were previously mentioned, it is possible to conclude that Latin America requires its own way of thinking and implementation on marketing, and these should be linked and rooted to the organizational culture of every company and every country. It is important that the marketing theories and trends can be understood as a systemic process that involves all the areas of a company and can create processes of innovation and competitive advantages adapted to each one of the business scenarios.